ANALYSIS OF BANK SOUNDNESS LEVEL USING RGEC METHOD BEFORE AND AFTER THE IMPLEMENTATION OF PSAK 71 - Purnamasari, Dian Indri; Retina Claranita, Adelia Prima (International Journal of Research -GRANTHAALAYAH, 2021)
The changing economic conditions require dynamic regulations on economic system in order to keep the pace of economic growth. By the dynamic nature we mean making constant changes in economic aspects in efforts to adapt to the current conditions. An example could be the bank regulation which is an important institution in distributing funds to concerned parties. The present study aims to determine the differences in bank soundness level before and after the implementation of PSAK 71 in Indonesian commercial banks. We adopted assessments of Risk Profile, Earnings, Good Corporate Governance and Capital. The study used 21 samples collected using a purposive sampling approach. To analyze our data we used descriptive statistics, normality test, and paired t-test. The results indicate that differences were found between all ratios before and after the implementation of PSAK 71, except NPL ratio.